(untitled) (Journal of the College of Basic Education, 2022)
This research is concerned with the study of (adapting the textual structure to visual rhetoric in the formations of Arabic calligraphy) because of the technical specifications of Arabic calligraphy that help build these formations, as well as the method or style that distinguishes it, so that it appears with internal structural transformations that make it away from the idea of ​​direct reception, Taking long distances with unconventional artistic indications with visual eloquence.Through the exploratory study, the research and the models that were obtained, the researcher was able to raise the problem of his research in the first chapter of his study by asking the following question: Is it possible to adapt the textual structure to visual rhetoric in the structure of Arabic calligraphy formations?